How you have done it is just fine- just post any questions and in time I'm sure they will be answered.

For this particular problem:

Derive equations for the sum, sum for two at a time, and product of roots. [I will use a, B and aB as the roots] These will give you:

1. (aB)^2=d

2. a+B+aB= b

3. aB(1+a+B)=c

Adding 1 and 3 together we get

c+d= aB+a^2 B+ aB^2 + (aB)^2

Factorising:

c+d= aB(1+a+B+aB)

Squaring both sides we get

(c+d)^2= (aB)^2 (1+a+B+aB)^2

Now we sub in our initial pro-numerals

(c+d)^2 = d(1+b)^2

## Bookmarks